A presença de uma trepadeira invasora influencia a dispersão de uma palmeira nativa através de interferência em suas interações com a avifauna? - Feitosa, Sara Soares (2024)
The establishment of invasive plants in new areas is responsible for negatively affecting the richness and recruitment of native species. The impacts arising from invasion can be spread to groups that interact with native plants. Nonetheless, this interaction is essential for the reproduction and dispersal of native plants, in addition to being responsible for providing important resources for the fauna. Although the direct impacts of invasive plants on native plants are well elucidated, little is known about the interference in the reproductive aspects of native plants through their influence on interspecific interactions with fauna. To fill this gap, the main objective of this research was to investigate whether the presence of the invasive liana Cryptostegia madagascariensis Bojer ex Decne (Apocynaceae) interferes in the way the fauna interacts with the native palm tree Carnaúba Copernicia prunifera (Miller) H. E. Moore (Arecaceae), to impact seed dispersal and seedling recruitment. To do this, we selected an invaded area and an area without invasion in two municipalities. In each area, we demarcated focal points and focal individuals to record interactions between plants and fauna. Under the canopy of the selected focal individuals located in different areas, we positioned seed collectors and quantified the number of seedlings to assess the effect of the infestation on seed dispersal and seedling recruitment. The infestation did not affect the quantity of fruits deposited in the collectors and the number of inflorescences with fruits in different individuals. The reproductive aspect of the native plant exclusively modified by invasion was the seedling quantity. In areas without infestation, focal individuals presented greater numbers of seedlings under the canopy. Regarding the impacts on birds, there was a decline in the abundance of interactions and species richness in invaded areas, regardless of the period. Most species interacted exclusively with native palm individuals in areas without infestation, thus the spread of invasion by invasive lianas could result in loss of habitat for these species. In addition to these parameters, the invasive liana promoted compositional changes in the species that visited invaded areas and caused a reduction in functional diversity. The impact on the abundance of interactions did not translate into changes in the number of fruits in the seed collectors, this indicates that the bird species registered did not act as dispersers of the native palm tree fruits. Despite not influencing interspecific interactions in a way that causes changes in seed dispersal, invasive lianas directly impact seedling recruitment and bird species. Considering the negative effects on different groups caused by invasive lianas, the control of these plants is essential for maintaining ecosystem functioning.